Regional trends of aerosol optical depth and their impact on cloud properties over Southern India using MODIS data. (August 2016) - Gopal, K. Rama; Obul Reddy, K. Raja; Balakrishnaiah, G.; Arafath, S.MD.; Kumar Reddy, N. Siva; Rao, T. Chakradhar; Reddy, T. Lokeswara; Reddy, R. Ramakrishna
Abstract: Remote sensing of global aerosols has constituted a great scientific interest in a variety of applications related to global warming and climatic change. In the present study we investigate the spatial and temporal variations of aerosol optical properties and its impact on various properties of clouds over Southern India for the last ten years (2005–2014) by using Moderate Resolution Imaging Spectroradiometer (MODIS) data retrieved from the onboard Terra and Aqua satellites. The spatial distributions of annual mean lowest Aerosol Optical Depth (AOD) value is observed in Bangalore (BLR) (0.22±0.04) and the highest AOD value is noted in Visakhapatnam (VSK) (0.39±0.05). Similarly high Fine Mode Fraction (FMF) is noticed over VSK and Thiruvananthapuram (TVM), while lower values are observed in Anantapur (ATP), Hyderabad (HYD), Pune (PUNE) and BLR. From the results, a negative correlation was found between AOD and Cloud Top Temperature (CTT), Cloud Top Pressure (CTP) where as, a positive correlation was observed between AOD and Cloud Fraction (CF), Water Vapor (WV) over the selected regions. Monthly average AOD and FMF are plotted for analysis of the trends of aerosol loading in a long-term scale and both values showed statistically significant enhancing trend over all regions as derived from the MODIS measurements. Further, the annual variation of spatial correlation between MODIS and MISR (Multi - Angle Imaging Spectro Radiometer) AOD has been analyzed and the correlation coefficients are found to be higher in two of the regions VSK and PUNE (>0.8), and considerably lower for TVM (<0.7). Highlights: A significant south-to-north latitudinal gradient in AOD is noticed over South India. AOD varies seasonally from low in the winter to high in summer and monsoon. Correlation between AOD and cloud parameters is identified. The annual increasing trend in AOD and FMF are observed in all regions.